Highly-stable write-once-read-many-times switching behaviors of 1D–1R memristive devices based on graphene quantum dot nanocomposites - Sung, Sihyun (Sci Rep, 2018)
One diode and one resistor (1D–1R) memristive devices based on inorganic Schottky diodes and poly(methylsilsesquioxane) (PMSSQ):graphene quantum dot (GQD) hybrid nanocomposites were fabricated to achieve stable memory characteristics. Current-voltage (I-V) curves for the Al/PMSSQ:GQDs/Al/p-Si/Al devices at room temperature exhibited write-once, read-many-times memory (WORM) characteristics with an ON/OFF ratio of as large as 10(4) resulting from the formation of a 1D–1R structure. I-V characteristics of the WORM 1D–1R device demonstrated that the memory and the diode behaviors of the 1D–1R device functioned simultaneously. The retention time of the WORM 1D–1R devices could be maintained at a value larger than 10(4) s under ambient conditions. The operating mechanisms of the devices were analyzed on the basis of the I–V results and with the aid of the energy band diagram.